Right heart catheterisation is still a fundamental part of the follow-up assessment of pulmonary arterial hypertension. Issue 1 (5th July 2018) - Humbert, Marc; Weatherald, Jason
For patients with pulmonary arterial hypertension (PAH), the most recent European guidelines state that right heart catheterisation (RHC) is mandatory for confirming the diagnosis of PAH, and that RHC should be considered 3–6 months after therapy changes and in patients who experience clinical deterioration [1, 2]. The guidelines also mention that some centres perform RHC at regular intervals during follow-up [1, 2]. However, many centres across the world do not routinely monitor invasive haemodynamic variables during follow-up, for a variety of potential reasons including the invasive nature of the test, cost or availability. We argue that, based on current data, RHC is still an indispensable component of the clinical management and follow-up of PAH patients in the current treatment era. Right heart catheterisation is still a fundamental part of the follow-up assessment of pulmonary arterial hypertension http://ow.ly/BUUi30kbbM5